(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was conducted at the Department of Soil, Water and Environment, University of Dhaka, from 10 January to 24 February 2021, to evaluate the growth parameters, biomass production, and nutrient uptake of red amaranth (Amaranthus tricolor L.) as influenced by different types of organic manures manufactured by companies, viz. ACI, Agro, Kazi, Mazim, McDonald, Naafco, Paragon and Sharib, and by 50% of recommended dose of NPK fertilizers. The experiment consisted of ten treatments with three replications each and was laid out in a Completely Randomized Design (CRD). On the day of harvest, Naafco displayed the greatest number of leaves (10.67±2.31), the longest leaf length (8.60 ± 2.07 cm), and the largest leaf area (275.10±118.8 cm2 plant-1), whereas the highest plant height (24.53±3.27cm) and stem girth (24.53±3.27cm) were observed in McDonald. Conversely, Kazi exhibited the poorest performance in all aforementioned parameters. Both the highest fresh and dry weights (10.75±6.09 g plant-1 and 1.31±0.87 g plant-1 respectively) were recorded in Naafco treated plants, and the lowest weights in Kazi (1.98 g plant-1 and 0.23 g plant-1 respectively). The highest total nutrient content (NPKS and Fe) (46.02 mg plant-1) in plants was found in Naafco, while the lowest was in Kazi (3.96 mg plant-1). Judging from the results, Kazi treated plants consistently showed the lowest growth, biomass, and nutrient accumulation. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 73-82